2008
DOI: 10.1029/2008je003083
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to special section on the Phoenix Mission: Landing Site Characterization Experiments, Mission Overviews, and Expected Science

Abstract: Phoenix, the first Mars Scout mission, capitalizes on the large NASA investments in the Mars Polar Lander and the Mars Surveyor 2001 missions. On 4 August 2007, Phoenix was launched to Mars from Cape Canaveral, Florida, on a Delta 2 launch vehicle. The heritage derived from the canceled 2001 lander with a science payload inherited from MPL and 2001 instruments gives significant advantages. To manage, build, and test the spacecraft and its instruments, a partnership has been forged between the Jet Propulsion La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 45 publications
0
92
0
5
Order By: Relevance
“…At the same latitudes, landforms possibly as young as one million years old have been interpreted as evidence of recent localized reworking of the martian surface by the action of near-surface ground ice (Malin and Edgett, 2000;Baker, 2001;Mustard et al, 2001). Direct evidence of the presence of ground ice at high latitudes (68.22°N) on Mars has been provided by the Phoenix lander (Arvidson et al, 2008), which found widespread icy soil only a few centimeters below the surface, under a desiccated layer of soil (Smith, 2009). Although this ice was found at high latitude, its presence reinforces the possibility of the existence of similar icerich ground in the mid-latitudes, possibly in lower amounts and/ or at a greater depth.…”
Section: Introductionmentioning
confidence: 97%
“…At the same latitudes, landforms possibly as young as one million years old have been interpreted as evidence of recent localized reworking of the martian surface by the action of near-surface ground ice (Malin and Edgett, 2000;Baker, 2001;Mustard et al, 2001). Direct evidence of the presence of ground ice at high latitudes (68.22°N) on Mars has been provided by the Phoenix lander (Arvidson et al, 2008), which found widespread icy soil only a few centimeters below the surface, under a desiccated layer of soil (Smith, 2009). Although this ice was found at high latitude, its presence reinforces the possibility of the existence of similar icerich ground in the mid-latitudes, possibly in lower amounts and/ or at a greater depth.…”
Section: Introductionmentioning
confidence: 97%
“…NASA's Mars Phoenix spacecraft (Smith et al 2008(Smith et al , 2009 . Equipped with the Surface Stereo Imager (SSI), with adequate resolution to image dust devils, and a high-resolution pressure sensor, Phoenix became the second Mars lander, after Pathfinder, that had the capacity to detect dust devils both visually and by meteorological measurements.…”
Section: Mars Phoenix Landermentioning
confidence: 99%
“…For an overview of the Phoenix mission, see Smith et al [2008]. The suite of scientific instruments Phoenix is bringing to Mars will enable it to better understand the history of Martian water by examining the chemistry and mineralogy of arctic soils and ice.…”
Section: Introductionmentioning
confidence: 99%